Configuration interaction studies on the spectroscopic properties of PbO including spin-orbit coupling - 罗旺 李瑞 盖志强 艾瑞波 张宏民 张晓美 闫冰 (Chinese physics B, 2016)
Lead oxide（Pb O）, which plays the key roles in a range of research fields, has received a great deal of attention. Owing to the large density of electronic states and heavy atom Pb including in Pb O, the excited states of the molecule have not been well studied. In this work, high level multireference configuration interaction calculations on the low-lying states of Pb O have been carried out by utilizing the relativistic effective core potential. The effects of the core-valence correlation correction, the Davidson modification, and the spin–orbital coupling on the electronic structure of the Pb O molecule are estimated. The potential energy curves of 18 Λ-S states correlated to the lowest dissociation limit（Pb（~3P_g） ＋ O（~3P_g）） are reported. The calculated spectroscopic parameters of the electronic states below 30000 cm~（-1）, for instance, X~1Σ~＋, 1~3Σ~＋,and 1~3Σ~-, and their spin–orbit coupling interaction, are compared with the experimental results, and good agreements are derived. The dipole moments of the 18 Λ-S states are computed with the configuration interaction method, and the calculated dipole moments of X~1Σ~＋and 1~3Σ~＋are consistent with the previous experimental results. The transition dipole moments from 1~1Π, 2~1Π, and 2~Σ to X~1Σ~＋and other singlet excited states are estimated. The radiative lifetime of several low-lying vibrational levels of 1~1Π, 2~1Π, and 2~1Σ~＋ states are evaluated.